Advanced spoken English - Sood, Madan (New Delhi : Goodwill Publishing House)
Advanced Spoken English by our revered author, Madan Sood, is meant not only for improving writing skills but also for oral practice. It is useful for both the advanced and the average learners who have completed at least the basic course in English. The content is so chosen and the exercises are so framed as the learners are sure to learn what they require. The exercises in the book have been framed to make learning a fun and easy process. We are sure that the book would prove immensely useful for the readers.
Keywords: English language -- Spoken English; English language -- Textbooks for foreign speakers